The use of geomatic techniques to monitor environmental deformation - Samih Al Rawashdeh; Rami E. Al Ruzouq; Khaldoun S. Qtaishat (International Journal of Science and Engineering, 2013)
Geospatial deformations are very important in some countries and may lead to catastrophes. For this purpose we need to find practical accurate ways to provide continuous monitoring and measurement to allow protection and secure safety. Some countries are suffering great losses such as Jordan where the major high way that connects the north to the middle of the country is closed most of the winter due to landslides that push the road away. In this work we are employing new Geomatics technique to analyze, monitor and measure the landslides. An application of geodetic monitoring of a major landslide on the highway linked Amman to the north (Jerash, Irbid). For the purpose of monitoring the landslide we designed a geodetic network, which consists of 4 points. Measurements were carried out over the period 2007 to 2012 (before and after rainy season) of 12 points within the network. The obtained results are compared to results published previously using different techniques of measurement over the two years period (2002-2004). In the new methodology, GPS receivers and total stations of high precision were used in addition to an orthophoto of two aerial photographs. The observations adjustment and the deformation analysis were executed using locally developed computer programs. The study enabled us to determine a value of 0.26 m/year as an average displacement of the landslide-prone area for the period of 2007-2012. Doi: 10.12777/ijse.4.2.2013.92-96 [How to cite this article: Rawashdeh, S.,  Ruzouq, R.E., and Qtaishat, K.S.. (2013). The use of geomatic techniques to monitor environmental deformation.  International Journal of  Science and Engineering, 4(2),92-96. Doi: 10.12777/ijse.4.2.2013.92-96]